2014
DOI: 10.1098/rspa.2014.0107
|View full text |Cite
|
Sign up to set email alerts
|

Supra-molecular assembly of aromatic proton sponges to direct the crystallization of extra-large-pore zeotypes

Abstract: The combination of different experimental techniques, such as solid 13 C and 1 H magic-angle spinning NMR spectroscopy, fluorescence spectroscopy and powder X-ray diffraction, together with theoretical calculations allows the determination of the unique structure directing the role of the bulky aromatic proton sponge 1,8-bis(dimethylamino)naphthalene (DMAN) towards the extra-large-pore ITQ-51 zeolite through supra-molecular assemblies of those organic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…3a) is likely assigned to DMAN complexes, which are expected in the crystalline environment of the IFO structure; indeed, self-assembled DMAN aggregates filling the IFO pores have been found by Rietveld and molecular simulation studies. 50 The recorded emission spectra upon excitation to this band (l exc = 460 nm and l exc = 550 nm, Fig. 3c) confirm the formation of two weakly emissive complexes: one centered at around 540 nm and another at longer wavelengths at around 650 nm (similar to the emission band found in solution, Fig.…”
Section: Synthesis Of Mg-itq-51 and Photophysics Of Occluded Dmansupporting
confidence: 68%
See 1 more Smart Citation
“…3a) is likely assigned to DMAN complexes, which are expected in the crystalline environment of the IFO structure; indeed, self-assembled DMAN aggregates filling the IFO pores have been found by Rietveld and molecular simulation studies. 50 The recorded emission spectra upon excitation to this band (l exc = 460 nm and l exc = 550 nm, Fig. 3c) confirm the formation of two weakly emissive complexes: one centered at around 540 nm and another at longer wavelengths at around 650 nm (similar to the emission band found in solution, Fig.…”
Section: Synthesis Of Mg-itq-51 and Photophysics Of Occluded Dmansupporting
confidence: 68%
“…This is a typical feature of interCT complexes but not of excimers, as the latter only exist in the excited electronic state because they dissociate after photon emission. Therefore, the incorporation of the structure-directing agent DMAN takes place both in its monomeric (although in a minor extension) and associate states (which should represent the main species present according to the previous Rietveld study 50 and to our experimental packing of 2.0 DMAN/u.c., as determined from TGA and CHN analyses and photometric method), resulting in feasible self-interactions of the DMAN molecules in the synthesis gel and the final Mg-ITQ-51 solid prepared. 50 On the other hand, a highly fluorescent material has been obtained as a consequence of the enhanced photophysical properties of the constrained monomer units.…”
Section: Synthesis Of Mg-itq-51 and Photophysics Of Occluded Dmanmentioning
confidence: 51%
“…Therefore, it can be concluded that proton sponges are an interesting group of compounds to study. These features often receive credit in materials chemistry [ 71 ], as well as in catalysis, such as in the activation of CO [ 72 ]. A relatively small number of available experimental and theoretical studies, as well as short interatomic separation in the N-H⋯N moiety [ 64 ], large values of the N– N coupling constants [ 64 , 65 , 66 ], and other interesting physico-chemical features of DMANH and its derivatives, prompted us to investigate the dynamic nature of the intramolecular hydrogen present in the investigated “proton sponges” (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of crystallized zeolites containing 16-ring pores reveals the difficulties of finding appropriate OSDAs able to stabilize this type of channels [12]. However, the bulky OSDAs formed by the particular supramolecular self-assembling of two aromatic DMAN molecules in the synthesis media show the adequate shape and size to stabilize the formation of 16-ring pores by proper host-guest interactions during nucleation and crystallization processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, the bulky OSDAs formed by the particular supramolecular self-assembling of two aromatic DMAN molecules in the synthesis media, show the adequate shape and size to stabilize the formation of 16-ring pores by proper host-guest interactions during nucleation and crystallization processes. [10] *Author for correspondence (acorma@itq.upv.es, mmoliner@itq.upv.es ). Unfortunately, the silicoaluminophosphate form of the ITQ-51 shows low Brønsted acidity because the isomorphic substitution of Si atoms within the SAPO material resulted in the formation of large "silicon islands" in the zeolitic frameworks, [6] and it has been broadly described that these silicon-rich areas show very low Brønsted acidity.…”
Section: -Introductionmentioning
confidence: 99%